Dynamical factors affecting ozone mixing ratios in the Antarctic lower stratosphere - Shiotani, Masato; Gille, John C. (1987)
An account is given of the climatology and interannual variability of dynamical quantities and ozone mixing ratios during the Southern Hemisphere spring for 1979-1984. The seasonal variation in temperature in the lower stratosphere is repeatable; a steep decrease in zonal mean ozone mixing ratios is observed around 60 deg S toward the South Pole in September which, with time, becomes shallower in association with minor warmings and a final warming. Climatological synoptic charts in the lower stratosphere show the circumpolar circulation in the geopotential height field and the prominence of planetary wave 1 in the temperature and ozone fields. When wave activity is strong, there are weaker westeries, higher temperatures, and higher ozone mixing ratios at high latitudes.